Reduced signaling of PI3K-Akt and RAS-MAPK pathways is the key target for weight-loss-induced cancer prevention by dietary calorie restriction and/or physical activity - Standard, Joseph; Jiang, Yu; Yu, Miao; Su, Xiaoyu; Zhao, Zhihui; Xu, Jianteng; Chen, Jie; King, Brenee; Lu, Lizhi; Tomich, John; Baybutt, Richard; Wang, Weiqun (My University, 2014)
Weight control through either dietary calorie restriction (DCR) or exercise has been associated with cancer prevention in animal models. However, the underlying mechanisms are not fully defined. Bioinformatics using genomics, proteomics and lipidomics was employed to elucidate the molecular targets of weight control in a mouse skin cancer model. SENCAR mice were randomly assigned into four groups for 10 weeks: ad-libitum-fed sedentary control, ad-libitum-fed exercise (AE), exercise but pair-fed isocaloric amount of control (PE) and 20% DCR. Two hours after topical TPA treatment, skin epidermis was analyzed by Affymetrix for gene expression, DIGE for proteomics and lipidomics for phospholipids. Body weights were significantly reduced in both DCR and PE but not AE mice versus the control. Among 39,000 transcripts, 411, 67 and 110 genes were significantly changed in DCR, PE and AE, respectively. The expression of genes relevant to PI3K-Akt and Ras-MAPK signaling was effectively reduced by DCR and PE but not AE as measured through GenMAPP software. Proteomics analysis identified ~120 proteins, with 27 proteins significantly changed by DCR, including up-regulated apolipoprotein A-1, a key antioxidant protein that decreases Ras-MAPK activity. Of the total 338 phospholipids analyzed by lipidomics, 57 decreased by PE including 5 phophatidylinositol species that serve as PI3K substrates. Although a full impact has not been determined yet, it appears that the reduction of both Ras-MAPK and PI3K-Akt signaling pathways is a cancer preventive target that has been consistently demonstrated by three bioinformatics approaches.
Citation: Standard, J., Jiang, Y., Yu, M., Su, X., Zhao, Z., Xu, J., … Wang, W. (2014). Reduced signaling of PI3K-Akt and RAS-MAPK pathways is the key target for weight-loss-induced cancer prevention by dietary calorie restriction and/or physical activity. The Journal of Nutritional Biochemistry, 25(12), 1317–1323. https://doi.org/10.1016/j.jnutbio.2014.07.010
Keywords: Bioinformatics; Weigh Control; Cancer Prevention; Dietary Calorie Restriction; Exercise